Blemish of place: Territorial stigmatization and the depreciation of displaced villagers' resettlement houses in Chengdu, China. (October 2021) - Zhang, Mengzhu; Qiao, Si; Yeh, Anthony Gar-On
Abstract: In the 2010s, China witnessed a return of the state in land acquisition and urban (re)development processes. This return of the state has resulted in a new type of neighborhood, namely displaced villagers' resettlement community (DVRC), which is well built by the government and located close to middle-income communities' amenities. The displaced villagers are entitled to full ownership and sale right of their resettlement houses. However, these houses in DVRCs are depreciated in the housing market. This study examines and explains the housing depreciation in DVRCs with a combination of quantitative hedonic models and qualitative field investigations. We explain the housing depreciation in DVRCs through the lens of territorial stigmatization theory. Based on the findings, we argue that the housing depreciation DVRCs is caused by the entrenched prejudice towards the peasantry in Chinese society. This prejudice has mutated into territorial stigmatization of DVRCs as uncivilized and poor neighborhoods. This paper innovatively bridges territorial stigmatization thesis and housing price research to provide a new method to reveal territorial stigmatization in the context of rising market approach to social housing. It contributes to the debate on whether social mix development can avoid the stigmatization of social housing communities. Highlights: China witnessed a return of the state in land acquisition and urban (re)development processes. This return of the state has resulted in a new type of urban neighbourhood, namely displaced villagers' resettlement community (DVRC). This study examines and explains the housing depreciation in DVRCs. The depreciation phenomenon in DVRCs is caused by the entrenched prejudice towards the peasantry in Chinese society. This prejudice has mutated into territorial stigmatisation of DVRCs as 'uncivilised and poor neighbourhoods'